Temporal variation in the population characteristics of harvested wolverine (Gulo gulo) in northwestern Canada - Piia M. Kukka; Thomas S. Jung; Jean-François Robitaille; Fiona K. A. Schmiegelow (Wildlife Research, 2017)
Context. Wolverines (Gulo gulo) are harvested for fur in northern Canada; however, the impacts of harvest are poorly known. Additionally, wolverine population data are largely absent for much of their northern range. Demographic data collected from harvested wolverines provide information on the vulnerability and variability of different sex and age cohorts to harvest, which, in turn, may have implications for harvest sustainability.Aims. We examined the temporal variability of different sex and age cohorts in wolverine harvest among years, and within the harvest season, in Yukon, Canada. We also examined the pregnancy status of female wolverines in relation to the harvest date, so as to evaluate the impact of the harvest-season length on breeding wolverines.Methods. We determined the sex and age composition of harvested wolverines via dissections of 655 carcasses collected from 2005 to 2014. We determined the reproductive status and fetal measurements for female wolverines via dissections of reproductive tracts.Key results. The harvest consisted mostly of males, particularly of young individuals. The sex ratio of harvested animals did not fluctuate significantly, but we observed variation in the age structure among years. The age structure varied within the harvest season (November to March), with a greater proportion of adults being harvested in late winter. Active gestation was evident in females harvested after mid-January, and near-term or postpartum females were harvested during late February and March.Conclusions. Late winter harvest is likely to have a more significant impact on populations than is early winter harvest, because of increased harvest of adults and breeding females. Wolverine harvest season extends to the onset of the denning season in late February and March, indicating a concern for ethical harvest.Implications. Limiting the legal harvest season to early winter may contribute to improved harvest sustainability and protection of breeding wolverines in northern latitudes.